2018
DOI: 10.1111/bjd.16445
|View full text |Cite
|
Sign up to set email alerts
|

Updates in lichen sclerosis: British Association of Dermatologists guidelines for the management of lichen sclerosus 2018

Abstract: Linked Article: Lewis et al. Br J Dermatol 2018; 178: 839–853

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 15 publications
(22 reference statements)
0
21
0
6
Order By: Relevance
“…According to the British Association of Dermatologists (BAD) Guidelines for the management of LS, which were updated in 2018, recommended treatment for anogenital LS in women is with clobetasol propionate 0.05% ointment. 44,49 This is based upon evidence from randomized control trials that found that clobetasol propionate ointment 0.05% is more effective in the treatment of vulvar LS compared to topical tacrolimus 0.1%, topical testosterone 2%, and phototherapy, and equally effective as mometasone furoate 0.1%. [50][51][52][53] The recommended dose is a half-fingertip unit (approximately 0.5 g) applied to the affected area once daily for 1 month, then every other day for 1 month, and then twice weekly for a third month.…”
Section: Ultrapotent Topical Corticosteroidsmentioning
confidence: 99%
“…According to the British Association of Dermatologists (BAD) Guidelines for the management of LS, which were updated in 2018, recommended treatment for anogenital LS in women is with clobetasol propionate 0.05% ointment. 44,49 This is based upon evidence from randomized control trials that found that clobetasol propionate ointment 0.05% is more effective in the treatment of vulvar LS compared to topical tacrolimus 0.1%, topical testosterone 2%, and phototherapy, and equally effective as mometasone furoate 0.1%. [50][51][52][53] The recommended dose is a half-fingertip unit (approximately 0.5 g) applied to the affected area once daily for 1 month, then every other day for 1 month, and then twice weekly for a third month.…”
Section: Ultrapotent Topical Corticosteroidsmentioning
confidence: 99%
“…According to the recommendations of the British Association of Dermatologists, it is recommended to use 0.05% clobetasol propionate ointment in combination with an emollient for three months, with the following gradual dose-reduction scheme during the therapy: once a day in the first month of treatment, then every second day for a month, and two times a week during the third month of treatment. Children diagnosed with vulvar lichen sclerosus should receive long-term care—with lesions controlled three and then six months after the start of the therapy [ 36 , 42 ]. Additionally, according to the studies results, a follow-up visit is recommended after four weeks of therapy, to assess the effectiveness and safety of the treatment and the occurrence of possible complications, such as stretch marks, atrophic skin changes, and secondary reproductive tract infections.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Additionally, according to the studies results, a follow-up visit is recommended after four weeks of therapy, to assess the effectiveness and safety of the treatment and the occurrence of possible complications, such as stretch marks, atrophic skin changes, and secondary reproductive tract infections. The maximum allowable dose of clobetasol propionate is about 10 g per month [ 36 , 40 , 42 , 43 ]. According to the European guidelines for the treatment of vulvar lichen sclerosus, based on the EBM principles (evidence-based medicine principles), the proposed first-line treatment in girls is an ointment with 0.05% clobetasol propionate [ 23 ].…”
Section: Pharmacotherapymentioning
confidence: 99%
“…29 guidelines. [34][35][36] Patients should promptly be referred to a dermatologist and urologist in the event of urinary symptoms.…”
Section: Differential Diagnosis Of Bxomentioning
confidence: 99%
“…Daily use of potent topical corticosteroids (TCS) is the recommended first‐line therapy for BXO in adult males and boys, for example, one fingertip unit of 0.05% clobetasol propionate ointment, as per the British Association of Dermatology (BAD) guidelines . Patients should promptly be referred to a dermatologist and urologist in the event of urinary symptoms.…”
Section: Treatmentmentioning
confidence: 99%